The sociality of minimizing involvement in self-service shops in Denmark: Customers' multi-modal practices of being, getting, and staying out of the way. Issue 2 (April 2022) - Rasmussen, Gitte; Kristiansen, Elisabeth Dalby
For some customers, the corona pandemic has turned e-shopping into a fine alternative to shopping in brick-and-mortar shops. For other customers in quarantine e-shopping is the only alternative. The long-lasting pandemic, however, has reminded us of the importance of social contacts and interactions – even if it's just to go the supermarket to 'mingle'. This paper investigates what 'mingle' means when shopping in physical self-service shops amongst unacquainted others in Denmark. It describes customers' practice of doing self-service by organizing interaction to minimize social involvement. It shows how they, as a matter of fact, co-ordinate their conduct in ways that hampers possibilities for engaging in even small 'ritual' exchanges of talk. The paper draws upon a corpus of video recordings of customers' self-service practices in shops in Denmark. In addition, the customers' gaze was recorded with the mobile Tobii Pro X3 eye tracker. The study falls within the realm of ethnomethodological and conversation analytic studies of multimodal interaction. It concludes that self-service is achieved through co-present customers' tacit coordination of multimodal actions in social interaction and that their practices work to achieve 'effortlessly' and 'spontaneously' being, getting, and staying out of the way, which seems to be an ideal for self-service shopping. Talk and moreover having a conversation seems to be an impediment to it.